Prevalence and Incidence of Sexually Transmitted Infection in Injectable Progestin Contraception Users in South Africa - Noguchi, Lisa M.; Marrazzo, Jeanne M.; Richardson, Barbara; Hillier, Sharon L.; Balkus, Jennifer E.; Palanee-Phillips, Thesla; Nair, Gonasagrie; Panchia, Ravindre; Piper, Jeanna; Gomez, Kailazarid; Ramjee, Gita; Chirenje, Z. Mike (Frontiers in Reproductive Health, 2021)
Introduction Whether intramuscular depot medroxyprogesterone acetate (DMPA-IM) and norethisterone enanthate (NET-EN) have differential impact on incident sexually transmitted infection (STI) remains unclear. In VOICE, HIV-1 acquisition was higher for DMPA-IM versus NET-EN users. We compared DMPA-IM and NET-EN users with regard to chlamydia, gonorrhea, trichomoniasis, syphilis, and herpes simplex virus type 2 (HSV-2) infection. Materials and Methods Prospective data were analyzed from VOICE, a randomized trial of HIV-1 chemoprophylaxis. Participants were evaluated annually and as indicated for chlamydia, gonorrhea, trichomoniasis, and syphilis. Stored specimens were tested for HSV-2. Proportional hazards models compared STI risk between DMPA-IM and NET-EN users. Results Among 2,911 injectable contraception users in South Africa, 1,800 (61.8%) used DMPA-IM and 1,111 used NET-EN (38.2%). DMPA-IM and NET-EN users did not differ in baseline chlamydia: 15.1 versus 14.3%, p=0.54; gonorrhea: 3.4 versus 3.7%, p=0.70; trichomoniasis: 5.7 versus 5.0%, p=0.40; or syphilis: 1.5 versus 0.7%, p=0.08; but differed for baseline HSV-2: (51.3 versus 38.6%, p<0.001). Over 2,742, 2,742, 2,783, 2,945, and 756 person-years (py), respectively, 448 incident chlamydia, 103 gonorrhea, 150 trichomonas, 17 syphilis, and 48 HSV-2 infections were detected (chlamydia: 16.3/100 py; gonorrhea 3.8/100 py; trichomoniasis 5.4/100 py; syphilis 0.6/100 py; HSV-2 6.4/100 py). Comparing DMPA-IM to NET-EN users, no difference was noted for incident chlamydia, gonorrhea, trichomoniasis, syphilis, or HSV-2 infections, including when adjusted for confounders (chlamydia [aHR 1.03, 95% CI 0.85 to 1.25], gonorrhea [aHR 0.88, 95% CI 0.60 to 1.31], trichomoniasis [aHR 1.07, 95% CI 0.74 to 1.54], syphilis [aHR 0.41, 95% CI 0.15 to 1.10], HSV-2 [aHR 0.83, 95% CI 0.45 to 1.54, p=0.56]). Discussion Among VOICE participants in South Africa, DMPA-IM and NET-EN users differed in prevalence of HSV-2 at baseline, but did not differ in incident chlamydia, gonorrhea, trichomoniasis, syphilis, or HSV-2 infection. Differential HIV-1 acquisition previously demonstrated in this cohort does not appear to be explained by differential STI acquisition. However, high incidence of multiple STI reinforces the need to accelerate access to comprehensive sexual and reproductive health services.